How to unite local initiatives for a more sustainable global future - Vasilis Kostakis; Nikiforos Tsiouris (Sustainable Futures, 2024)
This article challenges the belief in high-tech solutions to solve socio-environmental crises, proposing a political vision beyond ''green growth'' and ''ecomodernism.''. It advocates for a commons-based technology framework, promoting collective resource management for sustainability. We thus introduce ''cosmolocal'' production, a configuration that strives to connect communities around shared resources and serve their needs while minimizing ecological impact. Despite acknowledged tensions, we contend that the cosmolocal framework could foster institutional and social change, aiming to address environmental degradation and wealth inequality. To support this contention on cosmolocal production's potential, we point to several successful examples from the open-source technology paradigm.